The use of green synthesis for obitenting silver nanoparticles from sunflower extracts (Helianthus annuus) (Research, Society and Development, 2021)
The synthesis of silver nanoparticles has been attracting attention due to its properties and applications in various fields of science.These nanoparticles can be produced by different methods using green synthesis. What results in the minimization of the production cost of the nanoparticles. Thus, this work aimed to synthesize silver nanoparticles (AgNPs) stabilized in sunflower extracts (Helianthus annus). The production of the nanoparticle was carried out in agitation on a magnetic plate heated until the total configuration of the nanoparticle, at the end the vejetal extract was used to stabilize it. They were characterized using UV-VIS. The antimicrobial analysis of the nanoparticles was performed in a petri dish with the measurement of the size of the inhibitory halo formed. AgNPs were obtained in the UV-vis spectra around 20 nanometers. It was verified through the absorption peaks that it varied - 414 nm to 422 nm (λmax 422 nm) that the extract of Helianthus annuus was able to stabilize with effect of formation of halo on the lines of S. aureus (16 mm), E coli (12 mm) and P. aeruginosa (10 mm), while AgNPs that were not stabilized with sunflower did not present the inhibitory halo. Through this research it was possible to prove that green synthesis (SV), despite being a new nanotechnological product with sustainable bases, is an excellent alternative with a high reproducibility and is in accordance with the principles of green chemistry, presenting itself as an alternative of low cost-effective, eco-friendly and biocompatible in the synthesis of AgNPs. In addition to serving as a subsidy for further research.